2016
DOI: 10.1186/s13063-015-1132-0
|View full text |Cite
|
Sign up to set email alerts
|

Early biliary decompression versus conservative treatment in acute biliary pancreatitis (APEC trial): study protocol for a randomized controlled trial

Abstract: BackgroundAcute pancreatitis is mostly caused by gallstones or sludge. Early decompression of the biliary tree by endoscopic retrograde cholangiography (ERC) with sphincterotomy may improve outcome in these patients. Whereas current guidelines recommend early ERC in patients with concomitant cholangitis, early ERC is not recommended in patients with mild biliary pancreatitis. Evidence on the role of routine early ERC with endoscopic sphincterotomy in patients without cholangitis but with biliary pancreatitis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 42 publications
0
22
0
4
Order By: Relevance
“…Recently, a multicentre RCT* comparing routine early ERC plus ES with conservative treatment in 232 patients with predicted severe acute biliary pancreatitis but without cholangitis was completed and results are awaited (the APEC-trial, ISRCTN97372133). 70…”
Section: Early Phase Of Acute Pancreatitismentioning
confidence: 99%
“…Recently, a multicentre RCT* comparing routine early ERC plus ES with conservative treatment in 232 patients with predicted severe acute biliary pancreatitis but without cholangitis was completed and results are awaited (the APEC-trial, ISRCTN97372133). 70…”
Section: Early Phase Of Acute Pancreatitismentioning
confidence: 99%
“…AP is an acute disease, and the incidence rate increases proportionally with age. 24 Data from an emergency department (ED) showed that ageing patients aged over 65 years old diagnosed with AP comprised one-third of all patients. 8 Another registry study reported a six-fold increase in the incidence of AP patients aged over 80 years over a decade.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have advocated early ERCP intervention in all patients with (predicted) severe biliary pancreatitis (61,62), however this has not become standard of care (10,47). The multicentre APEC trial is currently studying the impact of routine early (<24 hours) ERCP in predicted severe biliary pancreatitis (63). There is consensus that patients with mild and moderate AP do not require early ERCP (62), as potential benefits do not outweigh the procedural risks.…”
Section: Special Considerationsmentioning
confidence: 99%